The Effect of Work Discipline and Motivation toward Civil Servant’s Performance in Kerenci Regency Regional Secretariat - Beni Setiawan; Syamsir Syamsir; Afriva Khaidir (Fakultas Ilmu Pendidikan UNP)
This study aims to reveal the effect of work discipline motivation on civil servants performance working at Kerinci Regency Regional Secretariat. because there is a problem the employee performance it is proven by preliminary data that researchers get there are still targets that have not been fully realized. This research used quantitative method. The population of this study was all civil servants serving in the Kerinci Regency Regional Secretariat. Respondents in this study were amounted to 95 samples. The data collection technique used in this study was proportional stratified random sampling technique. The data was collected through questionnaires that have been tested of their validity and reliability in advance, both the content and empirical test items in the field. Data analysis technique used in this research was multiple regressions. The results showed that there is a significant effect of work discipline and motivation on Kerinci Regency Regional Secretariat civil servants performance. This means that higher-level work discipline and motivation will improve civil servants performance.